Theoretical and practical continuity in the making of Ottoman/Turkish literary history: a metahistoriographical analysis - Vissing, E (2020)
The practice of literary historiography in the Ottoman Empire and Turkey is considered to be a relatively recent phenomenon, the emergence of which is thought to take place in the early twentieth century. Mehmed Fuad Köprülü (1890-1966) is widely acknowledged as a pioneer of the discipline. Neither the period preceding Köprülü’s input, nor the aftermath of his impact have yet come under the spotlight of rigorous scholarly research. There have been no comprehensive analytical surveys of the corpus, with a comparative perspective that evaluates the works in and of themselves as well as their similarities and differences, which could reveal the evolution of the theoretical and practical aspects of the making of Ottoman/Turkish literary history.